2021
DOI: 10.1088/1361-6463/ac203c
|View full text |Cite
|
Sign up to set email alerts
|

Parylene-based memristive synapses for hardware neural networks capable of dopamine-modulated STDP learning

Abstract: Nowadays there is a growing interest in wearable and biocompatible computing systems that are safe for the human body. Memristive devices are prospective for such tasks owing to a number of their attractive properties, in particular, the multilevel character of resistive switching, or plasticity, which allows them to emulate synapses in hardware neuromorphic networks (NNs). The use of local learning rules for such NNs, for example, bioinspired spike-timing-dependent plasticity (STDP), has firmly established it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 49 publications
0
4
0
1
Order By: Relevance
“…We have previously shown that single memristors work successfully as a part of spiking networks, for example, for associative learning [26]. In addition, in our previous work, we have also successfully demonstrated that both single and crossbar PPX memristors can change their conductance according to the rules of dopamine-modulated STDP rule, and therefore are an important link in the implementation of hardware reinforcement learning [32]. Here we have successfully demonstrated the training of a formal network based on a new improved type of crossbar array of PPX memristors.…”
Section: Resultsmentioning
confidence: 82%
See 1 more Smart Citation
“…We have previously shown that single memristors work successfully as a part of spiking networks, for example, for associative learning [26]. In addition, in our previous work, we have also successfully demonstrated that both single and crossbar PPX memristors can change their conductance according to the rules of dopamine-modulated STDP rule, and therefore are an important link in the implementation of hardware reinforcement learning [32]. Here we have successfully demonstrated the training of a formal network based on a new improved type of crossbar array of PPX memristors.…”
Section: Resultsmentioning
confidence: 82%
“…But for the use of memristors in CMOS-compatible hardware neural networks, single structures are unsuitable, and a crossbar topology is required for integration into computational microelectronics [30]. PPX-based memristors can also be realized in arrays of crossbar structures [31,32]. But a detailed study of such structures was not carried out, therefore the purpose of the work was a comprehensive study of the main memristive characteristics, as well as the development of new methods for creating crossbar arrays of PPX-based memristors.…”
Section: Introductionmentioning
confidence: 99%
“…We have previously demonstrated that PPX-based memristors without inclusions can be successfully used to construct NCSs. ,, The enhancement of all main characteristics due to the addition of MoO x should undoubtedly lead to an increase in the neuromorphic potential of the memristors. For the neural network modeling, we selected a representative taskMNIST handwritten digits classificationand employed a typical network architecture: a fully connected two-layer network (784 × 512 × 10; see the Methods section for further details).…”
Section: Resultsmentioning
confidence: 99%
“…Продемонстрированы результаты по исследованию устойчивости обучения СНС к вариабельности характеристик мемристоров как аналоговых элементов, а также к использованию шума в качестве конструктивного фактора при обучении и удержании мемристивных весов импульсной сети [7,11]. Обсуждаются также подходы к реализации локальных правил дофаминоподобного обучения с подкреплением в СНС, которые необходимы для формирования аналога системы «потребностей» интеллектуального агента в процессе его автономного функционирования [12][13][14]. Рассмотрены первые результаты по созданию прототипа мемристивного имплантируемого устройства, нейропротезирующего двигательную активность животного [15,16].…”
Section: аннотацияunclassified